Kolaborasi Sekolah dan Masyarakat dalam Pembelajaran Bahasa untuk Peningkatan Kualitas Pendidikan SMP dan SMA di Kabupaten Enrekang - Amir, Johar; Dalle, Ambo; Angreany, Femmy; Fachrul Syaputra, Arlian; Azizah, Laelah (Jurnal Pengabdian Masyarakat, 2025)
This program explores how collaboration between schools and local communities can meaningfully enhance language learning and improve the overall quality of education at the junior and senior high school levels. Recognizing that language is key to communication and critical thinking, the research draws on foundational theories such as Vygotsky’s social interaction theory, Bandura’s social learning theory, Freire’s critical pedagogy, and the concept of authentic learning by Herrington, Reeves, and Oliver. Using a qualitative case study approach, the research involved students, teachers, school leaders, and community members selected purposively. Data were gathered through participant observation, in-depth interviews, and document review, and analyzed thematically. The findings reveal a strong positive impact of school-community collaboration. Around 85% of students showed noticeable improvement in speaking skills, while 92% of educators reported increased student motivation. Community involvement in language activities also rose significantly from 30% to 78%. Moreover, 88% of students felt they gained a deeper understanding of the cultural and social context of the language, and 90% expressed greater confidence in using the language in real-life situations. These results highlight how real-world interactions with the local community can bring language learning to life, making it more relevant and engaging for students. The study recommends that schools continue building meaningful partnerships with communities, supported by consistent programs and government policies. Further research is also encouraged to explore the long-term benefits of such collaborative efforts in education.